Land Regularization and Community Development Nexus in Cities of Sub Saharan Africa: A Critical Review with Urban Growth and Development Perspectives - Zakayo, Edmund; Mhache, Emmanuel Patroba; Wakuru, Magigi (International Journal of Scientific Research and Management (IJSRM), 2018)
Land regularization is an emerging urban planning tool which is directly linked to community development, particularly when one want to acquire title deed in unplanned settlements in cities of Sub-Saharan Africa. This paper contributes knowledge base critically with a view on land regularization and community development reviews in cities growth and development processes perspectives. Different urban planning approaches and modes have been discussed to provide a base for critical analysis and understanding in the context of land regularization and community development nexus, interlinkages and their impacts in Sub-Saharan Cities for learning and replications.